Skeletal manifestations of renal disease in childhood. Issue 4 (July 2016) - Denburg, Michelle R.
Abstract : Purpose of review: This review summarizes recent findings on musculoskeletal health in three chronic renal conditions of childhood: chronic kidney disease stages 2–5D, nephrotic syndrome, and urolithiasis. Findings with important clinical implications warranting further investigation are highlighted. Recent findings: Recent cohort studies have demonstrated a high burden of fracture and progressive deficits of cortical bone in children with chronic kidney disease. Lower cortical density is associated with incident fracture and may be an important therapeutic target. Parathyroid hormone and calcium are independent correlates of cortical density, and modifiable factors for fracture include parathyroid hormone and phosphate binder use. Children with nephrotic syndrome, even with normal renal function, have evidence of abnormal bone metabolism and structure, and vitamin D deficiency may be an important modifiable risk factor in this population. Urolithiasis has been associated with reduced bone mineral density and is increasingly common in children and adolescents. Population-based data found a significantly increased risk of fracture in adolescent males and young women. Summary: Recent findings substantiate concern regarding the particular vulnerability of the growing skeleton to chronic renal disease. Studies are needed to determine how to optimize assessment and management of bone health in children with these conditions, particularly in terms of calcium and vitamin D requirements, with the goal of improving childhood bone accrual for lifelong fracture prevention.